An Electrochromic Nickel Phosphate Film for Large-Area Smart Window with Ultra-Large Optical Modulation - Pengyang Lei; Jinhui Wang; Yi Gao; Chengyu Hu; Siyu Zhang; Xingrui Tong; Zhuanpei Wang; Yuanhao Gao; Guofa Cai (Nano-Micro Letters, 2023)
Highlights Transition metal phosphates were first developed for the electrochromic application. The obtained NiHPO4·3H2O film achieves an ultra-large optical modulation of 90.8%, and the electrochromic mechanism is systematically elucidated using in situ and ex situ techniques. A large-area electrochromic smart window with 100 cm2 is constructed, which displays superior performances in regulating natural lighting and storing electrical charges.